Integration of Islamic Values, Mathematics, and Career Readiness Competencies of Prospective Teachers in Islamic Universities - Siti Inganah; Nopia Rizki; Choirudin Choirudin; Syed Muhammad Yousaf Farooq; Novi Susanti (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
This study aims to investigate career readiness towards understanding the integration of Islamic values and mathematics in prospective mathematics teacher students who are studying at Islamic tertiary institutions. This study involved 375 students consisting of 71 males (19%) and 304 females (81%). Data collection tool by providing an online questionnaire with Google Form related to demographics (place of education, age, and gender), a questionnaire about the integration of Islamic values with mathematics and a career readiness questionnaire for prospective mathematics teachers. Data analysis using part analysis with SPSS. The results showed that there was no direct influence between understanding the integration of Islamic values and mathematics on the competence and career readiness of future mathematics teachers at Islamic tertiary institutions. Students tend to find it difficult to say that between religion and mathematics teachers who are most responsible for teaching mathematics with Islamic values. They are not sure of the competence they have to relate the content of Islamic values to mathematics. In the realm of professional competence, students feel confused about how to start teaching the relationship between Islamic values and learning mathematics in class and when the application is taught.